Antidepressant Use and the Risk of Major Adverse Cardiovascular Events in Patients Without Known Cardiovascular Disease: A Retrospective Cohort Study - Jang, Ha Young; Kim, Jae Hyun; Song, Yun-Kyoung; Shin, Ju-Young; Lee, Hae-Young; Ahn, Yong Min; Oh, Jung Mi; Kim, In-Wha (Frontiers in Pharmacology, 2020)
Aims: Conflicting data exist on whether an association exists between antidepressants and the risk of major adverse cardiovascular events (MACEs) in patients with depression. This may be due to the use of various study designs and residual or unmeasured confounding. We aimed to assess the association between antidepressant use and the risk of MACEs while considering various covariates, including severity of depression and the cardiovascular disease(CVD) risk score. Methods: Patients newly diagnosed with depression with no history of ischemic heart disease and stroke were followed-up from 2009 to 2015. We conducted Cox proportional hazard regression analysis to estimate hazard ratios (HRs) for each antidepressant for MACE risk. Result: We followed-up (median, 4.4 years) 31,830 matched patients with depression (15,915 antidepressant users and 15,915 non-users). In most patients (98.7%), low-dose tricyclic antidepressants (TCAs) were related with a significantly increased risk of MACEs (adjusted HR = 1.20, 95% confidence interval [CI] = 1.03-1.40). Duration response relationship showed a gradually increasing HR from 1.15 (95% CI = 0.98-1.33; <30 days of use) to 1.84 (95% CI = 1.35-2.51; ≥ 365 days of use) (P for trend<0.01). High Korean atherosclerotic CVD risk score (≥7.5%) or unfavorable lifestyle factors (smoking, alcohol intake, and exercise) were significantly associated with MACEs. Conclusion: Even at low doses, TCA use was associated with MACEs during primary prevention. Longer duration of TCA use correlated with higher HR. Careful monitoring is needed with TCA use in patients with no known CVD history.